MODEL MANAJEMEN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DKI JAKARTA, BANTEN, DAN JAWA BARAT - Sufyati Sufyati; Atsari Sujud (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
This research aims to design a management model in order to strengthen the capacity and creativity in the organization PKBM. The results of this first phase of research is in the form of a conceptual model that contains elements of management PKBM strengthening the capacity and creativity of the organization based on the diversity of local wisdom. Management model that the researchers expected, namely: 1) Strengthening the management capacity in the sense of empowering managers, both in the context of an individual and as a group. This concept can be done through training, seminars, workshops and the like. 2) Strengthening the capacity of the program carried out in the form of modification programs to be executed, the government and the entire program synergize PKBM components that include: educators, administrative staff, parents /guardians of prospective learners, potential learners, steakholder of business and industry. 3) Strengthening the overall value system by helping the target and make the rules among stakeholders PKBM accordance with local wisdom (local wisdom) each of which may be different between the CLC with each other. 4) Improve the empowerment of CLC through effectiveness and track record of alumni become an important part, it is the first step helps to build networks and partnerships PKBM strong in the future.